THE CHALLENGING OF DIAGNOSIS, TREATMENT, AND EDUCATION IN PATIENT WITH BUERGER’S DISEASE: A CASE REPORT FROM REMOTE AREA: THE CHALLENGING OF DIAGNOSIS, TREATMENT, AND EDUCATION IN PATIENT WITH BUERGER’S DISEASE: A CASE REPORT FROM REMOTE AREA - Rianda, Rama Azalix; Satryawan, Heri; Mozes, Jacquels (Lombok Health And Science Journal, 2024)
Background: Thromboangiitis obliterans (TAO) or Buergerâ€™s Disease is a chronic inflammatory disease. If not treated early and adequately, TAO can result in limb amputation. The study regarding TAO in women is rare and limited. Also how difficult it is to diagnose and educate patients with TAO, especially in remote areas Case Presentation: A 38-year-old woman came to the emergency room with the chief complaint of pain and darkening in toes and hands 2 months ago, especially when it is cold. The patient did not come to the public health facility but was treated with traditional medicine according to local beliefs. History of smoking was denied. The localized status was found gangrene in toes and fingers, ulcer in toes, and oedema in legs. Allen’s tests were positive. Dorsalis pedis arteries were palpable. ABI wasnâ€™t performed. Laboratory examination showed an increased liver function. Cardiomegaly, Lung oedema, and minimal right pleural effusion were shown in Chest X-ray. History taking, clinical finding, and laboratory finding suggested the patient to amputation but the patient refused it. The Patient was treated by antibiotic, analgetic, anticoagulant, and double. After 3 days of treatment, the patient was discharged and asked to return to the outpatient care for education about amputation. Discussion: Most patients are aged 20-45 years. Men are more common than women. The etiology of TAO is unknown, but cigarette exposure is still associated with TAO. The role of hypercoagulability in the pathogenesis of TAO has been proposed. Elevated plasma homocysteine has been reported in patients with TAO. There was a strong link between the plasma Hcy concentration and Liver Fibrosis. We assessed the patient with TAO regarding suspect hypercoagulability affected by increased liver function. Difficult to diagnose due to patient denied smoking history and other imaging and laboratory tests werenâ€™t performed. Patients with TAO who have elevated homocysteine also have a higher rate of amputations. Education is a key role for understanding the concept of health. Countries with higher education levels are more likely to have better national health conditions. We can conclude that lower levels in tertiary education affects a countryâ€™s health situation in terms of premature mortality. Conclusion: It is difficult to diagnose Buerger’s disease or thromboangiitis obliterans because of the atypical complaints, minimal risk factors, and limited facilities for imaging and other laboratory tests. The difficulty of educating patients to get the best treatment is also a challenge for general practitioners, especially in remote areas Keywords: Buergerâ€™s disease, thromboangiitis obliterans, woman, remote area, education level